2018
DOI: 10.1002/celc.201801148
|View full text |Cite
|
Sign up to set email alerts
|

Size Tunable Zeolite‐Templated Carbon as Microporous Sulfur Host for Lithium‐Sulfur Batteries

Abstract: Spatial confinement of sulfur in porous carbons has been one of the major approaches to address the polysulfide (PS) shuttle problem of lithium‐sulfur (Li−S) batteries. Among them, microporous carbon can effectively confine sulfur inside pores, however, it shows low active material utilization due to pore blockage by discharge products. To address this issue, in this work, zeolite‐templated carbons (ZTCs) with high surface area and electronic conductivity are used as host material for Li−S battery and their pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…In S/HPCS (CS 2 /IPA), in which the sulfur is loaded in the mesopore shell, there may be pore clogging during the discharging reaction. It has been observed that pore clogging in a zeolitetemplated microporous carbon host results in low performance at a high rate (52). S/HPCS (CS 2 /NMP) is capable of ion transfer to the interior via the mesopore shell, which may allow relatively high utilization of sulfur.…”
mentioning
confidence: 99%
“…In S/HPCS (CS 2 /IPA), in which the sulfur is loaded in the mesopore shell, there may be pore clogging during the discharging reaction. It has been observed that pore clogging in a zeolitetemplated microporous carbon host results in low performance at a high rate (52). S/HPCS (CS 2 /NMP) is capable of ion transfer to the interior via the mesopore shell, which may allow relatively high utilization of sulfur.…”
mentioning
confidence: 99%
“…The particle size of the MOFs also exerts a significant influence on the performance of the LSB. [141][142][143][144][145][146][147] A smaller particle size not only promotes electron transport but also provides a larger contact area with the electrolytes and conductive additives. [148][149][150][151] However, as the particle size decreases, leaching of the soluble polysulfides is accelerated, which further complicates the situation.…”
Section: Appropriate Particle Sizementioning
confidence: 99%
“…Zeolite-templated nanocarbon materials have also been applied as cathode of the lithium-sulfur battery. [276,277] Lithium-sulfur (Li-S) batteries have become one of the most promising alter-natives of LIBs for next-generation energy storage devices due to its overwhelming theoretical energy density (≈2600 Wh kg −1 ), low cost, and environmental friendliness. Currently, there are obvious shortcomings.…”
Section: Lithium-sulfur Batteriesmentioning
confidence: 99%
“…prepared a series of microporous carbons with various particle sizes from 20 to 400 nm, but identical micropore size of 1.4 nm, to investigate the particle size effect for cathodes of Li–S batteries. [ 277 ] The sample with smallest particle size exhibit optimal capacity of 1199 mAh g −1 and high cycling stability. For the case of microporous carbons with larger particle sizes, Li 2 S was generated at the entrance of the micropores, thereby limiting discharging capacity.…”
Section: Energy Applications Of Nanocarbon Materials Templated By Zeomentioning
confidence: 99%